STRATEGY FOR IMPLEMENTING ISLAMIC RELIGIOUS EDUCATION TO INCREASE TOLERANCE BETWEEN STUDENTS IN SCHOOLS - Mustaghfiroh, Ana; Mubaroq, Muhammad Syahrul; Zubaidi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the application of participatory methods and multidimensional approaches in Islamic religious education at MI Raudlatussalam Besuk, Probolinggo, and their impact on increasing attitudes of tolerance among students. The main objective of this study is to identify how this learning method can shape students' characters to be more tolerant and respectful and live side by side in diversity. This study uses a descriptive qualitative approach with a case study at MI Raudlatussalam, involving interviews with the principal, religious teachers, parents of students, and student representatives, as well as direct observation of the learning process at school. The study results indicate that using participatory methods, which involve students actively in group discussions, joint projects, and extracurricular activities, has created an inclusive and harmonious learning environment. Students learn and apply religious values in daily interactions, including in interfaith relations. A multidimensional approach that combines various dimensions of learning, such as extracurricular activities and social interactions, has also proven effective in strengthening attitudes of tolerance. Parents and student representatives expressed that this approach positively impacted the development of students' characters, who were more open and empathetic towards differences. This study concludes that the participatory method and multidimensional approach applied at MI Raudlatussalam have succeeded in increasing the understanding and application of tolerance values and forming better student character in dealing with diversity.